Efecto del cálculo del impuesto a la renta por la imposición de la ley de simplicidad y progresividad tributaria en la editorial La Gaceta S.A. - Gavilánez Gavilánez, Víctor Israel (2022)
The purpose of this integrative project is to analyze the process of calculation, declaration and payment of income tax at Editorial La Gaceta S.A. for the period 2019 -2020, and its effects due to the imposition of the Law of Simplicity and Progressive Taxation, the research presents a comparative study on the methodology used for the calculation and payment of income tax before and after the imposition of the Law of Simplicity and Progressive Taxation. It is necessary to point out that the referred normative body contains an important change for the compliance of the tax in economic entities registered as micro-enterprises; to obtain real data, specific techniques were used to collect information; for the field research work, the survey addressed to the person in charge of the accounting was chosen, which helped to know the effects caused within the publishing house with the implementation of the new regime, obtaining results that allow issuing value judgments on the reform enacted by the Law, the incentive and facility that the micro-enterprises have for the payment of the income tax; producing a technical impact at the time of making the calculations for the liquidation of the income tax in view that one must have the appropriate knowledge to apply the tax reforms; either the General Regime and/or Micro-enterprise Tax Regime (MTR), it can be evidenced the great impact that has caused the application of the new tax regime, by virtue that the Editorial la Gaceta for the liquidation to the Income of the year 2019 applying the general regime and according to the economic activities developed during that year has managed to obtain a balance in favor of $ 3. 665.16 US dollars, for that in the year 2020 with the application of the new micro-entrepreneurial tax regime with its calculation of 2% regardless of whether the company tube profit or loss has generated a tax payable of $ 4,031.32 US dollars.